Identity, nationhood and state-building in Malaysia including "Regaining the middle ground in Malaysian politics" : a conversation with Patrick Pillai - Ratnam, K. J. (Strategic Information and Research Development Centre, 2019)
Identity, loyalty and nation building are key global challenges today. In the first part of this book, Emeritus Professor K.J. Ratnam, a leading Malaysian social scientist, discusses multiple identities in complex societies, political loyalty, and the challenges that ethnic and religious differences pose for social cohesion. In the second section of the book, done in conversational style, he talks to researcher-writer Patrick Pillai about the importance of regaining the middle ground in Malaysian politics. He expresses a clear preference for civic over ethnic nationalism, arguing that, by embracing all citizens, it provides a more sustainable basis for loyalty. Among key issues discussed are whether Malaysia is a 13-State or a three-State federation, democracy and governance, ethnic politics, and electoral reform. Professor Ratnam also analyses current political alignments and their impact on ethnic relations, the perils of ethnic stereotyping, and the need for a national consensus on foundational issues. He says visions, narratives, national ideologies and constitutions may be useful in bringing people together, but are not enough for holding them together, and suggests some practical ways this problem can be overcome. Sweeping in scope yet detailed in analysis, this publication will interest scholars, students, policy makers and laymen, and encourage reflection on useful ways of facing up to the many complex challenges confronting multi-ethnic and multi-religious societies like Malaysia.